What determines bank-specific variations in bank stock returns? Global evidence - Francis, Bill B.; Hasan, Iftekhar; Song, Liang; Yeung, Bernard (Journal of Financial Intermediation, 2015)
This paper examines how bank regulation and supervision measures affect the synchronicity of bank stock returns, a measure that is negatively related to variations in bank-specific fundamentals and stock price informativeness. Using data from World Bank surveys in 35 countries, we find that bank stock returns are less synchronous in countries with more stringent capital regulations, more supervision that emphasizes private monitoring, and less government bank ownership. On the other hand, direct government control of bank activities, as well as direct government monitoring and disciplining, do not reduce stock return synchronicity.